2022
DOI: 10.1111/mms.12986
|View full text |Cite
|
Sign up to set email alerts
|

Season, age, sex, and location impact the density of tooth rake mark and dorsal fin notch ofIndo‐Pacifichumpback dolphins (Sousa chinensis) in the northern South China Sea

Abstract: Tooth rake marks are usually used as an indicator of received aggression in odontocetes whose social interactions are difficult to observe directly. Photographic data from five locations of the northern South China Sea were used to analyze seasonal, demographic, and geographic effects on the density of tooth rake marks and dorsal fin notches in Indo-Pacific humpback dolphins (Sousa chinensis, IPHDs). The analysis revealed that fresh tooth rake marks were most frequent during the dry season. Males exhibited sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 99 publications
0
5
0
Order By: Relevance
“…The determination of the sex of IPHDs is more challenging since this species does not exhibit much sexual dimorphism. However, the sex of some individuals may be obtained through photographs taken during aerial behaviours, and both sex and reproductive status can be inferred through consistent association patterns with neonates or calves (Serres et al, 2022). During sea surveys (e.g., photo‐identification surveys), the dolphins' environment can be directly observed from the boat, including a wide range of human activities (i.e., presence of gillnets, aquaculture, boats and construction work; Wu et al, 2020; Piwetz et al, 2021), some aspects of water quality (i.e., floating marine debris; Zhou et al, 2011) and the social environment of dolphins (i.e., group composition and presence of dead calves; Wang et al, 2017; Liu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The determination of the sex of IPHDs is more challenging since this species does not exhibit much sexual dimorphism. However, the sex of some individuals may be obtained through photographs taken during aerial behaviours, and both sex and reproductive status can be inferred through consistent association patterns with neonates or calves (Serres et al, 2022). During sea surveys (e.g., photo‐identification surveys), the dolphins' environment can be directly observed from the boat, including a wide range of human activities (i.e., presence of gillnets, aquaculture, boats and construction work; Wu et al, 2020; Piwetz et al, 2021), some aspects of water quality (i.e., floating marine debris; Zhou et al, 2011) and the social environment of dolphins (i.e., group composition and presence of dead calves; Wang et al, 2017; Liu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The behavioural state of dolphins can be visually observed from the surface and categorized as foraging, socializing, milling, resting or traveling (e.g., Lin et al, 2021; Piwetz et al, 2021) and noticeable behaviours (i.e., playful or aggressive interactions, foraging in association with human activities and behavioural reaction towards boats; Chen et al, 2016; Zheng et al, 2016), and breathing sounds can be noted or videotaped if judged necessary. In addition to being used for photo‐identification purposes, photographs can be used to assess the dolphins' physical condition, including tooth rake marks (Serres et al, 2022), injuries and skin lesions (Serres, Lin, Liu, Lin, et al, 2023), and to detect unusual thinness (Lin, Wu, et al, 2022). When possible, aerial photogrammetry may inform more precisely on the body condition of IPHDs (Serres et al, 2024).…”
Section: Discussionmentioning
confidence: 99%
“…The higher prevalence of interspecific injuries found for dolphins from SWH may be linked with a higher predation level because of the open‐sea environment (Serres et al, 2022). Regarding LZB, one of the dolphin communities inhabiting this location has recently been found to be particularly subject to interactions with sharks which may influence these dolphins' social structure and behavior (Chen et al, in preparation).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, sex-related variation in prevalence was observed only with respect to orange patches; these were less common in females than males. Because male IPHDs exhibit higher densities of tooth rake marks than females (Serres et al, 2022), and because orange patches are often associated with fresh wounds including tooth rake marks (Onofre-Diaz et al, 2022), they may be more vulnerable to such skin conditions than females.…”
Section: Sexmentioning
confidence: 99%
“…Humpback dolphins in SWH had a pigmentation pattern similar to that in SNB but were different (more intense) compared with those in EZJ and PRE (Tang et al, 2021). Based on photo‐ID datasets, Serres et al (2022a, 2022b, 2022c) found that humpback dolphins from SWH, SNB, EZJ and PRE showed different levels of morphological skin features including shark bites, injuries, lesions, tooth rakes and dorsal fin notches. These morphological findings further illustrated the complex intraspecific variability of the morphological features of humpback dolphins in Chinese waters, which might result from long‐lasting geographical isolation and local environmental adaptations.…”
Section: Morphology and Behaviour: Additional Evidence To Support Pop...mentioning
confidence: 99%